Nizhny Novgorod Belyana barge in the XIX century - Philippov Yury V. (Zbornik Radova: Geografski institut "Jovan Cvijić", 2015)
The article discusses a unique Belyana barge, which was built in the Nizhny Novgorod region for several centuries. Belyana as a type of vessels was designed for transportation of logs, sleepers, beams, planks and other forest products from the Upper to the Lower Volga. Originally, the center of Belyana construction was the village of Baki, which was situated on the Vetluga River, a tributary of the Volga River. The Belyana construction technique spread from the Vetluga river banks further to Nizhny Novgorod, and then to Perm region. Almost all aspects of Belyana construction starting from the logging finishing with its floating to the lower Volga, and also cost of transported products in the prices of the XIX century are disclosed. Due to Belyana is truly a popular invention, it was built by traditional methods, relying solely on the centuries-old experience. Any drawings for the construction never existed, that’s why the author relied on preserved photographs and drawings in the historical reconstruction of this unique vessel. At the beginning of the article a brief overview of the geographical location of Nizhny Novgorod, as well as the names of wooden ships which were sailing on Volga and its tributaries in the same times with Belyana are given. At the end of the article practical recommendations on possible reconstruction of Belyana and using it as an interactive museum of ethnography are given.